2012
DOI: 10.1021/ac302223s
|View full text |Cite
|
Sign up to set email alerts
|

Amphipathic Polymers Enable the Study of Functional Membrane Proteins in the Gas Phase

Abstract: Membrane proteins are notoriously challenging to analyze using mass spectrometry (MS) because of their insolubility in aqueous solution. Current MS methods for studying intact membrane proteins involve solubilization in detergent. However, detergents can destabilize proteins, leading to protein unfolding and aggregation, or resulting in inactive entities. Amphipathic polymers, termed amphipols, can be used as a substitute for detergents and have been shown to enhance the stability of membrane proteins. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 36 publications
2
60
1
Order By: Relevance
“…The bacterial outer membrane enzyme PagP retains phospholipase activity after being trapped in SMALPs (Knowles et al 2009). OmpT and PagP are functional in A8-35 (Leney et al 2012). The transmembrane domain of the bacterial EII mtl mannitol permease performs the transphosphorylation from phosphoenolpyruvate to mannitol more rapidly after trapping in A8-35 than it does in detergent solution (Opačić et al 2014a).…”
Section: Basic Properties Of Amphipols and Membrane Protein/amphipol mentioning
confidence: 99%
See 3 more Smart Citations
“…The bacterial outer membrane enzyme PagP retains phospholipase activity after being trapped in SMALPs (Knowles et al 2009). OmpT and PagP are functional in A8-35 (Leney et al 2012). The transmembrane domain of the bacterial EII mtl mannitol permease performs the transphosphorylation from phosphoenolpyruvate to mannitol more rapidly after trapping in A8-35 than it does in detergent solution (Opačić et al 2014a).…”
Section: Basic Properties Of Amphipols and Membrane Protein/amphipol mentioning
confidence: 99%
“…At the date of this writing, seven α -helical MPs, including six GPCRs, have been folded in vitro using APols, and four β -barrel ones (see Table 7), with typical yields ranging between 60 and >90 %. For refolding from urea, the protocol generally involves diluting the urea-denatured protein into an APol solution, so as to lower the concentration of urea to non-denaturing levels (Dahmane et al 2011; Leney et al 2012; Pocanschi et al 2006, 2013). For refolding from SDS, the most usual procedure is to precipitate the dodecylsulfate as its potassium salt in the presence of APols (Bazzacco et al 2012; Catoire et al 2010a; Dahmane et al 2009, 2013; Pocanschi et al 2006).…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 c,d) that were successfully refolded directly into A8-35 [110]. Further studies revealed that the monomeric a-helical inner membrane proteins Mhp1 and GalP could also be liberated from amphipol A8-35 [89], and whilst the trimeric E.coli diacylglycerol kinase (DgkA) could be liberated from amphipol A8-35, the dominant species was the monomer (Fig.…”
Section: Amphipolsmentioning
confidence: 99%